The PCSK9 gene R46L variant is associated with lower plasma lipid levels and cardiovascular risk in healthy U.K. men. - Scartezini, M; Hubbart, C; Whittall, R; Cooper, J; Neil, A; Humphries, SE (2007)
In the present study, we have determined the relative frequency of the R46L, I474V and E670G variants in the PCSK9 (protein convertase subtilisin/kexin type 9) gene and its association with plasma lipid levels and CHD (coronary heart disease) in healthy U.K. men and patients with clinically defined definite FH (familial hypercholesterolaemia). Genotypes were determined using PCR and restriction enzyme digestion in 2444 healthy middle-aged (50-61 years) men from the prospective NPHSII (Second Northwick Park Heart Study), with 275 CHD events (15 years of follow-up), and in 597 U.K. FH patients from the Simon Broome Register. In the NPHSII healthy men, the R46L genotype distribution was in Hardy-Weinberg equilibrium and the frequency of 46L was 0.010 [95% CI (confidence interval), 0.007-0.013], with one man homozygous for the 46L allele. There was significant association of the 46L allele with lower mean (S.D.) total cholesterol [5.74 (1.01) mmol/l for RR compared with 5.26+/-1.03 mmol/l for RL; P=0.001], apolipoprotein B [0.87 (0.24) g/l for RR compared with 0.75 (0.26) g/l for RL; P<0.0001] and low-density lipoprotein cholesterol [4.01 (0.95) mmol/l for RR compared with 3.62 (0.97) mmol/l for RL; P=0.02]) levels, after adjustment for age, general medical practice, smoking, body mass index and systolic blood pressure. As expected, 46L carriers had a low risk of definite or possible CHD [hazard ratio, 0.46 (95% CI, 0.11-1.84)], but this was not statistically significant (P=0.27). Two other common PCSK9 variants I474V [V allele frequency, 0.179 (95% CI, 0.17-0.19)] and E670G [G allele frequency, 0.034 (CI, 0.03-0.04)] were not associated with any significant effects on lipid levels or CHD risk. In FH patients, the frequency of 46L was 0.003 (95% CI, 0.00-0.01), which was significantly lower (P=0.037) than the healthy subjects. In the four FH patients carrying 46L, mean untreated total cholesterol levels were not different (P=0.91) in carriers and non-carriers (median, 10.3 mmol/l compared with 10.2 mmol/l respectively, after adjustment for age, gender and mutation type). In conclusion, the PCSK9 46L allele is more frequent in healthy U.K. men than in FH patients and is strongly associated with a protective plasma lipid profile risk for CHD. Its low frequency (approx. 2% carriers) means that it does not make a major contribution to determining population CHD risk in the U.K.